Penerapan Lesson Study dalam Model Pembelajaran Berbasis Proyek (PJBL) untuk Meningkatkan Kreativitas Desain Logo Siswa Kelas 7h SMPN 1 Malang : Penelitian - Febiansi Wayu Lestari; Rully Aprilia Zandra (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Student creativity is essential in arts and culture learning activities, especially in the process of creating and designing logos. Creativity in design involves the integration of critical thinking, aesthetics, and originality, all of which can be developed through a learning process that promotes exploration and free expression. This study aims to enhance the creativity of 7H grade students at SMPN 1 Malang in designing logos through the implementation of a project-based learning (PjBL) model within the framework of a lesson study. The lesson study was conducted in three stages: planning, implementation, and reflection among teachers. The learning process focused on engaging students in the creation of original and innovative visual artworks. Students were given the opportunity to independently design logos based on their own ideas and creative expression. The findings of the study indicate that students showed significant improvement in the originality of their work, innovation in design, and technical skills. Additionally, the project-based approach contributed to increased active participation, self-confidence, and overall creative abilities.